If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7) * m + -1(9) * m = (-12) Multiply -1 * 9 7m + -9m = (-12) Combine like terms: 7m + -9m = -2m -2m = (-12) -2m = -12 Solving -2m = -12 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '-2'. m = 6 Simplifying m = 6
| x^2+5x+10=0 | | 3(w-2)-6w=-21 | | -2.06d+18=-10.48 | | 3a=144 | | 7m-9m=-12 | | x^2(x+9)+7(x+9)= | | -110=-4c-6c | | 3b+4=15 | | 5x+10=3x+24 | | 11x+(-6x)+11= | | 9r-8=6r+7 | | (x^4+y^2)(x^4-y^2)= | | 3(x+4)-(-4)=2x+8-4 | | 5x^6+5x^5-40x^4+35x^3= | | 2x-x=1.5 | | 4x-10=2x+12 | | x^2=(x-2)*(x+6) | | 3t+9t=60 | | m=n+8 | | 3x+5=5x-9 | | 7u+11.59=32.31 | | 3x+7=6x-11 | | 19x^7-8x^5+16x^4= | | 2x=(x-2)*(x+6) | | -3(1+2v)=90 | | (x-3)(x-1)(2x-5)=6 | | 3(2x-10)=-12 | | 2x*21=28(x+5) | | (x-3)(x-1)(2x-5)=12 | | -4a-6+5a=-3 | | 6x^6-7x^4+17x^3= | | 2x^3-x^2-16x+15=0 |